Patricia (Pat) Pocock (1940-2020) - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 2020)
It is with a heavy heart that we share that Patricia (Pat) Pocock RN, passed away on September 19th at the age of 80.